Multidisciplinary learning using mock trials. (5th May 2009) - Kessler, Gary C.; Simpson, Robert; Fry, James
In 2007, the Computer & Digital Forensics (C&DF), Criminal Justice (CJ) and Paralegal programs started to employ a mock trial to bring students from these three disciplines together. The event starts with a pre-planned crime scene. CJ students secure and process the crime scene, interview witnesses and gather evidence. Digital devices are recovered and are forensically processed by the C&DF students. Investigative reports are forwarded to Paralegal students who work with local attorneys who act in the role of the prosecution and defence teams. A retired criminal court judge presides over the proceedings, complete with a jury selected from volunteers from the college community. For many students, this is the first trial scenario they have seen outside of television.